Developmental Expression of Histone Deacetylase 11 in the Murine Brain - Liu, Hedi (2008)
Recent studies indicate that neural cell development in the central nervous system (CNS) correlates with a reduction in acetylation of histone core proteins. Moreover, histone hypoacetylation is thought to be important to oligodendrocyte lineage development. The mechanisms mediating the reduction in acetylation during postnatal neural development remain to be defined. To begin to understand these mechanisms, we investigated the expression of histone deacetylase 11 (HDAC11), a newly identified HDAC, in mouse brain during postnatal development. We show that HDAC11 was widely expressed in the brain and that this expression gradually increased in a region-specific pattern between birth and 4 weeks of age. At the cellular level HDAC11 protein was predominately localized in the nuclei of mature oligodendrocytes but only minimally in astrocytes. Although dentate gyrus granule neurons abundantly expressed HDAC11, granule neuron precursors in the subgranule layer exhibited little HDAC11 immunoreactivity. Double-immunostaining of the corpus callosum and dentate gyrus demonstrated that HDAC11 and Ki67, a cell-proliferating marker, are rarely colocalized in same cells. Our data show that HDAC11 was expressed in the developing brain in a temporal and spatial pattern that correlates with the maturation of neural cells, including cells of the oligodendrocyte lineage. These findings support a role for HDAC11 in CNS histone deacetylation and the development of oligodendrocytes and neurons during postnatal development.